THE THE ROLE OF UNIVERSITY IMAGE AND BRAND AWARENESS IN MEDIATING ANTECEDENTS OF STUDENTS' DECISION TO CHOOSE A UNIVERSITY - Yoga Kharisma, Alfin; Haryono, Tulus (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
In today's highly competitive environment, branding has become a major strategy for universities to differentiate themselves from competitors. By creating a strong and distinct brand image, universities can effectively control the level of competition and attract the attention of prospective students and stakeholders. This research analyzes the influence of promotions on social media, accreditation, study program prospects, facilities, education costs, and location on students' decisions in choosing a private university with brand awareness and university image as mediating variables. The sample used in this research were new students at a private university, namely Duta Bangsa University, Surakarta, Indonesia. The sampling technique used was proportional random sampling, and the number of samples taken was 318 new students. The analysis tool used is PLS-SEM. The findings in this research are that accreditation, study program prospects, location, and image influence students' decisions when choosing a university. Social media promotions, study program prospects, facilities, education costs, and location influence the university's image. Social media promotion, accreditation, and location influence brand awareness. Image mediates the influence of social media promotion, study program prospects, educational facilities, educational costs, and location on choosing a university. The implications of this research provide direction for university policies in carrying out effective branding strategies to improve prospective students' decisions in choosing a university.